PENGARUH KELAS UMUR TERHADAP PRODUKTIVITAS GETAH POHON PINUS MERKUSII DI KPH BANDUNG UTARA - Nirma Audina; Raizal Fahmi Solihat; Asep Purwanto (Fakultas Kehutanan Universitas Winaya Mukti, 2020)
This research was carried out in RPH Ujung Berung, BKPH Manglayang Barat KPH Bandung Utara, and Divisi Regional Jawa Barat & Banten. The time of the research was conducted from September to November 2018. The purpose of this study was to determine the effect the effect of age classes, diameter difference and interaction between age and diameter. Based on the results of the research it can be concluded that the productivity of pine resin is affected by the age class. It showed by data increased in age class followed by increased productivity of resin. Age Class IV is 13.26 grams, Age Class V is 30.74 grams and Age Class VI is 61.17 grams. There is a tendency for latex production to increase by the time the tree grow older to a certain age. Diameter affect the productivity of resin, the greater the growth of tree diameter, the more abundant the resin can be and the production of pine resin will increase. This is shown by data increased in diameter followed by increasing resin productivity, in diameters of 20-23 productivity of resin is 29.7 grams, diameter 24-27 productivity of resin is 36.44 grams and diameter 28-31 productivity of resin is 38.95 grams. Age classes difference affect the amount of resin production, the older the tree ages, the larger diameter will be, and finally affect to resin productivity, up to a certain age limit.